(untitled) (Malay Literature, 2016)
This article discusses the Hikayat Mareskalek as a work of etiquette literature intended to instruct the Malay rulers through a European character. The 18th/19th centuries were a time that saw the emergence of not only new types of writing but also new genres modelled on those introduced by the Europeans; the date of production of this hikayat falls during this time. Under the influence and patronage of Europe, transitional works such as these display a pro-European tendency in terms of the narrative point of view and he orientation of thought. However, fascination with Europe was not in fact total. Hikayat Mareskalek (Maarschalk Willem Daendels), written by Abdullah al-Misri in Pontianak in 1815, is one of the works that does not display such a tendency. Although this hikayat mentions a European in its title, he is not the subject of the narrative; instead the writer cleverly exploits and manipulates his characteristics, attitudes and actions to act as a "mirror" reflection for the Malay rulers. Keywords: Hikayat Mareskalek, Maarschalk Willem Daendels, etiquette genre, Abdullah al-Misri, reflection of Malay rulers